Pembatalan Putusan Badan Penyelesaian Sengketa Konsumen Akibat Wanprestasi Dalam Perjanjian Kredit - Lubis, Diana (Universitas Medan Area, 2024)
Consumer disputes arise because consumer rights are violated. Settlement of consumer disputes outside the court is carried out by dispute resolution institutions or by the parties themselves. This research is normative and legal in nature and is linked to the applicable laws and regulations. The library research method will be used for this research, and the data will be evaluated through qualitative analysis and written description. The Consumer Dispute Resolution Body is an institution tasked with handling and resolving disputes between economic actors and consumers. Since the settlement of bad credit disputes is not regulated in the mandate and authority of BPSK, the authority of the Consumer Dispute Settlement Body in settling defaults of credit agreements is not included in the scope of BPSK. BPSK misunderstood Article 52 of the Consumer Protection Law and exceeded its authority in resolving bad credit disputes.